Coping and resilience of rural and regional Australian immigrants: imperatives for successful settlement. Issue 2 (4th May 2017) - Penman, Joy; Goel, Kalpana
Abstract : This research provides an understanding of the coping strategies for successful settlement of Australian immigrants by elucidating key conceptual constructs relating to resilience development. Using qualitative descriptive methodology, 10 in-depth interviews with immigrants settling in regional South Australia between 2007 and 2012 were conducted. Thematic analysis was used to identify participants' meanings and realities associated with immigration and settlement. Five themes emerged around resilience, goals, settlement planning, healthy lifestyles and adaptation. A multidimensional conceptual model was created to capture how the immigrants coped and developed resilience. Findings offer insights for Australian immigrants, policymakers, and human service and health professionals, as well as academic researchers.